Promoting Solar Cell Efficiencies via Employing Sliver- Carbon- Pomegranate Peel Nano System (Baghdad Science Journal, 2019)
In this work, a functional nanocomposite consisting of multi walled carbon nanotubes combined with nanoparticles of silver and Pomegranate peel extract (MWCNTs- SNPs -NPGPE) was successfully synthesized using ultra sonic technique. The nanocomposite has been characterized using Transmission electron microscope (TEM), XRD, Energy dispersive X-ray spectroscopy (EDS) UV-Vis and FTIR. The obtained results reveal that the MWCNTs-SNPs-NPGPE nanocomposite exhibits form of nanotubes with rough surfaces and containing black spots, which are the silver nanoparticles. The dimensions of this tube are 161 nm in length and 60 nm in width with nanoparticles of silver not exceeding 20 nm. The XRD pattern of the prepared MWCNTs-SNPs-NPGPE nanocomposite showed four main peaks corresponding to the carbon nanotubes and planes of face centered cubic silver nanoparticles. The IR spectra referring to the(O-H) group stretching vibrations in carboxylic acid groups might come from NPGPE, and the stretching vibration of aliphatic C-H in carbon nanotubes. The carbon nanotube was used in solar cells (CNSCs) fabricated with and/or without fluorine-doped tin oxide (FTO) on the glass substrate with poly(3-hexylthiophene) (P3HT) and [6,6]-phenyl C61-butyric acid methylester (PCBM) blends (P3HT: PCBM). The FTO-(MWCNTs-SNPs-NPGPE / P3HT: PCBM/CNT/FTO-glass revealed more efficient CNSCs.